Epigenetics and the burden of noncommunicable disease: a paucity of research in Africa. (June 2015) - Hobbs, Angela; Ramsay, Michèle
Epidemiological evidence suggests that an adverse in utero environment is associated with an increased risk for developing adult onset diseases. The molecular mechanisms for susceptibility to chronic noncommunicable diseases are not fully understood, although recent research has proposed that epigenetic modifications play an important role in fetal programming. Genetic and environmental factors contribute to interindividual and spatiotemporal tissue-specific methylation patterns. Although the diverse environments and high genetic diversity of African populations provide unparalleled potential to investigate the effects of environmental change on the epigenetic profile in humans, only a small percentage of genomic and epigenetic studies have focused on populations from this continent. This emphasizes the need to build capacity in Africa for research that leads to an understanding of the association between genetic, epigenetic and environmental risk factors for noncommunicable diseases on the continent.